Sodium levels and immunotherapy efficacy in mRCC patients with bone metastases: sub analysis of Meet-Uro 15 study - Catalano, Martina; Rebuzzi, Sara Elena; Maruzzo, Marco; De Giorgi, Ugo; Buti, Sebastiano; Galli, Luca; Fornarini, Giuseppe; Zucali, Paolo Andrea; Claps, Melanie; Chiellino, Silvia; Zampiva, Ilaria; Pipitone, Stefania; et al. (Frontiers in Immunology, 2024)
Background: Immune-checkpoint inhibitors (ICIs) have significantly improved metastatic renal cell carcinoma (mRCC) prognosis, although their efficacy in patients with bone metastases (BMs) remains poorly understood. We investigated the prognostic role of natremia in pretreated RCC patients with BMs receiving immunotherapy.This retrospective multicenter study included RCC patients with BMs receiving nivolumab as second-line therapy or beyond. Inclusion criteria involved baseline sodium levels (pre-ICI) and sodium levels after 4 weeks of nivolumab initiation (post-ICI). The population was divided into two groups based on the median value, and response rates, progression-free survival (PFS), and overall survival (OS) were assessed.Results: Among 120 eligible patients, those with pre-treatment sodium levels ≥140 mEq/L showed longer OS (18.7 vs. 12.0 months, p=0.04). Pre-treatment sodium levels ≥140 mEq/L were associated with better OS compared to levels <140 mE/L (18.7 vs. 12.0, p=0.04). Post-treatment sodium levels ≥140 mEq/L were associated with improved PFS (9.6 vs. 3.2 months) and OS (25.1 vs. 8.8 months) (p=0.05 and p<0.01, respectively). Patients with consistent sodium levels ≥140 mEq/L at both time points exhibited the best outcomes compared to those with lower values (PFS 11.5 vs. 3.3 months and OS 42.2 vs. 9.0 months, respectively, p<0.01). Disease control rate was significantly higher in the latter group (p<0.01). Multivariate analysis confirmed the prognostic significance of sodium levels.Elevated sodium levels (≥140 mEq/L) pre-and post-ICI treatment correlate with better survival outcomes in mRCC patients with BMs. This finding suggests sodium level assessment as a potential prognostic factor in these patients and warrants further investigation, particularly in combination immunotherapy settings.